Fiscal Convergence in Africa: What Role for Regional Economic Communities? - Daouda Sembene; Vigninou Gammadigbe; Ismaël Issifou; Sampawende J.-A. Tapsoba (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
The literature on Optimal Currency Areas (OCA) has identified several channels for the ex post justification of common monetary areas based on the synchronicity criterion. These include trade, cross-border investments, mobility of factors, mobility of goods and services, and fiscal convergence of member countries. We focus on the later for the African continent. We analyze the role of African regional economic communities (RECs) in convergence of fiscal policies from 1990 to 2015. Our estimates show that African RECs reduce significantly fiscal divergence between countries. We further find that common monetary areas are more effective in fostering fiscal convergence. This result is in line with the argument of self-validation of monetary arrangements in Africa, despite low levels of cycle synchronization and trade intensity.
Keywords: E62; F15; O55; 330; Fiscal convergence; Common monetary areas; Africa